ANXIETY AND ITS RELATIONSHIP TO INJURY REHABILITATION PROGRAMS FOR FIRST-CLASS FOOTBALL PLAYERS - Ahmed Rahim Jassim; Zahraa jaffar husein; Sajjad kareem ghunaim (Galaxy International Interdisciplinary Research Journal, 2024)
Football is an attractive, exciting and at the same time risky sport, mixed with tension and physical struggle. According to another account, all who play this sport are at great risk of injury and with the knowledge of the potential risks to their health, due to the innumerable attractions of football, which are similar to those of another sport. The subject of anxiety occupies a major position in psychology in general and sports psychology in particular because of its clear and direct effects on the disruption of psychological functions, physical functions, or both .The study aimed to identify anxiety and its relationship to injury rehabilitation programs for first-class football players. And identifying the degree of anxiety and its relationship in rehabilitation programs for those injured in football. The importance of this research lies in taking into account the anxiety factor, which is an important and effective factor in rehabilitating football injuries .